Pedagogia Ojców Kościoła w ujęciu Siergieja Awierincewa. Z zagadnień recepcji chrześcijańskiego antyku we współczesnym pisarstwie rosyjskim - Banasiak, Daniel (Vox Patrum, 2022)
The article deals with the issue of being a disciple of Christ. The topic of the Church as a school, Jesus as a teacher, Christians as disciples and children of God was often taken up by the Fathers of the Church. Therefore, the article uses such patristic texts as: Paedagogus by Clement of Alexandria, Epistola encyclica, De incarnatione Verbi by Athanasius of Alexandria, De Sancta et Vivifica Trinitate, In psalmum XLVII by Theodoret of Cyrus, De Spirit of Sancto by Basil the Great, Vita Moysis by Gregory of Nyssa, De perfectione hominis by Efrem the Syrian. The article analyzes the essayist approach to patristic pedagogy in the text Mir kak shkola (1977) by Sergei Awierintsev, a Russian intellectual, fascinated by the legacy of early Christian authors. The analysis presents an essayistic approximation showing such issues as: the school of Christ’s disciples, the school of God’s children, the school of infants, the school of old and old children, the school of simplicity, the school of penance, the school of struggle. The research methodology is based here primarily on hermeneutical reading into texts (patristic, essayistic, poetic), but also on capturing Awierintsev’s essayistic optics, taking into account historical, socio-political, biographical and literary contexts. Sergey Awierintsev, who dealt with patristics in the unfavorable atheistic conditions of a totalitarian state, through his seemingly outdated and completely non-cyclical research on Christian antiquity, made a significant contribution to the spiritual revival of society in the days of the decline of the Soviet Union and the beginning of the political and economic transformation.